CAC scheme with imperfect power control in broadband CDMA networks - GAO Yong-hui1; ZHANG Dan-dan2 (Tongxin xuebao)
Putting forward the CAC schemes with imperfect power control for multimedia traffic would be great signifi-cant.The system capacity with imperfect power control and the other-cell to intra-cell interference factor was analyzed.And then considering the voice/video/data multimedia traffic scenario,a novel QoS（quality of service） based on CAC scheme was proposed.The simulation results show that the system capacity is heavily affected by the imperfect power control,and the proposed scheme can guarantee the QoS for different traffic efficiently,and improves the resource utility significantly.